آليات المحاججة و الإقتناء في الخطاب القرآني دراسة تداولية -سورة الكهف أنموذجا - مدلل, نجاح; غومة, سميرة; بوغزالة محمد, مريم (University of Eloued جامعة الوادي, 2024)
يعد الحجاج من أهم النظريات التي تهتم بها التداولية، ويرتكز على تقنيات وآليات يتبناها المتكلم للتأثير في المخاطب، وإقناعه بالموضوع، سواء أكانت هذه الآليات لغوية أو بلاغية أو شبه منطقية، وقد تضمنت سورة الكهف -محلّ الدراسة -معظم هذه الآليات، لكون السّورة جوابا وحجاجا للمنكرين للبعث، وتثبيتا للنّبي  وأصحابه. Al-Hajjaj is considered one of the most important theories that pragmatics is concerned with, and it is based on techniques and mechanisms adopted by the speaker to influence the addressee and convince him of the topic, whether these mechanisms are linguistic, rhetorical, or quasi-logical. Surah Al-Kahf - the subject of the study - included most of these mechanisms, because the Surah is an answer and an argument. For those who deny the resurrection, and in support of the Prophet, peace and blessings be upon him, and his companions.
لسانيات عامة
Keywords: آليات الحجاج-التداولية- الإقناع-الخطاب القرآني-سورة الكهف.; Record of pilgrims - pragmatics - persuasion - Quranic discourse - Surah Al-Kahf.